1990
DOI: 10.1161/01.hyp.15.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prostaglandins on papillary blood flow and pressure-natriuretic response.

Abstract: The present study examined whether renal prostaglandins influence the pressure-natriuretic response by altering medullary hemodynamics or renal interstitial pressure. The diuretic and natriuretic responses to changes in renal perfusion pressure were compared in control rats (n=15) and in rats receiving either meclofenamate (2 mg/kg, n=9) or indomethacin (2 mg/kg, n=4). In control rats, urine flow and sodium excretion increased from 10 ±2 to 118 ±10 jul/min/g kidney wt and from 1.8±0.3 to 21.0±1.5 /ieq/min/g ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 30 publications
3
61
0
Order By: Relevance
“…Our results could therefore be interpreted to mean that prostanoids and PAF do not play a significant role in pressure-natriuresis. In contrast, Roman and Lianos 17 have shown that inhibition of prostaglandin synthesis with indomethacin in rats blunted the pressure-natriuresis response. Karlstrom and colleagues 4 suggested that medullipin is natriuretic, and our previous study 3 also provided indirect evidence supporting this proposition.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our results could therefore be interpreted to mean that prostanoids and PAF do not play a significant role in pressure-natriuresis. In contrast, Roman and Lianos 17 have shown that inhibition of prostaglandin synthesis with indomethacin in rats blunted the pressure-natriuresis response. Karlstrom and colleagues 4 suggested that medullipin is natriuretic, and our previous study 3 also provided indirect evidence supporting this proposition.…”
Section: Discussionmentioning
confidence: 89%
“…15 The vasodilator prostaglandin E 2 is also made in the renal medulla 16 and has been shown to enhance sodium and water excretion from the kidney in response to increased renal perfusion pressure 17 and thus may contribute to the rapid fall in blood pressure after changes in renal perfusion pressure in this model. Furthermore, Ma and Dunham 18 have shown recently that cyclooxygenase products are the major vasodepressor substances produced by rat papillary tissue after incubation in vitro.…”
Section: Discussionmentioning
confidence: 97%
“…It is a potent vasodilator in both the peripheral (45) and renal vasculature (46). Moreover, PGE 2 has potent natriuretic effects in the kidney through direct epithelial effects on salt and water transport and as a consequence of its hemodynamic actions to increase renal blood flow (3,8). Accordingly, it has been suggested that inhibition of PGE 2 could explain the actions of NSAID and COX-2 inhibitors to cause edema and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…For example, infusion of PGE 2 into the kidney commonly causes renal vasodilation (2,3). PGE 2 also modulates renal sodium and water excretion (1,4).…”
mentioning
confidence: 99%
“…Atrial natriuretic peptide 2728 and the calcium channel blocker nisoldipine 29 can increase papillary blood flow in rats without altering cortical blood flow. In addition, cyclooxygenase inhibitors 30 and a kinin antagonist 15 have been reported to reduce papillary blood flow preferentially.…”
Section: Discussionmentioning
confidence: 99%